2015
DOI: 10.1097/jnr.0000000000000072
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Job Burnout Among Community Nurses in Changchun, China

Abstract: These results indicate that community nurses have a high rate of job burnout. Experts should be employed to train nurses in interpersonal communication skills. The community working environment should also be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 11 publications
4
21
1
13
Order By: Relevance
“…Workers with inefficient coping strategies for job stress and a feeling of little control of the situation also are more likely to feel ineffective in their work, and therefore, have a higher risk of burnout [14]. The results of sample characteristics are congruent with previous studies, observing that employees with permanent contracts show higher levels of emotional exhaustion than those with a temporary contract [23]. On the contrary, the data do not confirm that Work Shifts, Overwork or Time in the job had any significant relationship with CNA burnout scores.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Workers with inefficient coping strategies for job stress and a feeling of little control of the situation also are more likely to feel ineffective in their work, and therefore, have a higher risk of burnout [14]. The results of sample characteristics are congruent with previous studies, observing that employees with permanent contracts show higher levels of emotional exhaustion than those with a temporary contract [23]. On the contrary, the data do not confirm that Work Shifts, Overwork or Time in the job had any significant relationship with CNA burnout scores.…”
Section: Discussionsupporting
confidence: 79%
“…On the contrary, the data do not confirm that Work Shifts, Overwork or Time in the job had any significant relationship with CNA burnout scores. However, previous studies have shown that employees with permanent contracts and longer time in the job usually show burnout symptoms, which may be due to routine and monotony [23].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A study conducted among nurses in Liaoning province in northern China (n = 2613) showed similar results, and nurses below 30 years of age had the highest scores (Wu et al 2010). In another study from Liaoning, community nurses who experienced interpersonal relationship difficulties had higher burnout scores (Hu et al 2015), and new nurses appear to be more vulnerable to those difficulties (Chachula et al 2015). In Hong Kong, 168 nurses were surveyed with anxiety stress questionnaires.…”
Section: Introductionmentioning
confidence: 88%
“…In another study from Liaoning, community nurses who experienced interpersonal relationship difficulties had higher burnout scores (Hu et al . ), and new nurses appear to be more vulnerable to those difficulties (Chachula et al . ).…”
Section: Introductionmentioning
confidence: 99%